Criminalizing Non-Compliance with Civil Execution Orders: A Strategy for Enhancing Legal Certainty and Business Efficiency - Daim, Nuryanto Ahmad; Bayuaji, Rihantoro; Abadi, Suwarno (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
People seeking justice through civil justice often complain about legal uncertainty in terms of execution, because the execution procedure for civil cases does not have definite time period, especially when the Defendant takes other legal remedies such as opposition lawsuits and civil lawsuits, the execution process is also postponed. Moreover, when the losing party uses resistance methods in the execution time, the execution is also postponed. Therefore, this research aims to obtain the value of legal certainty regarding the implementation of the execution, because the losing party or related third parties can pursue a lawsuit against the execution which can prevent the execution. The target of this research is to create a policy model for resolving legal issues related to execution in order to create a sense of legal certainty and justice for the plaintiff (the winning party). The method used is normative juridical with a conceptual approach, statutory approach, comparative approach and philosophical approach. The findings of the research are that: non-compliance with legally binding decisions is still a form of civil contempt because it belongs to the civil domain, it is constructive (indirect) contempt because the execution of a civil case is the last part of the hearing process, so the action is id entified as disobeying a court order occuring when an act that should or should not be carried out by someone ordered or requested by the court in carrying out his or her functions cannot be fulfilled by the person who was ordered. So this unlawful act can be qualified as a criminal act as regulated in Article 281 paragraph (1) of Law Number 1 of 2023 on the Criminal Code (KUHP).